Distribusi Dana Zakat Infak dan Sedekah untuk Penguatan Pendidikan - Almaida, Nur (Civil Officium: Journal of Empirical Studies on Social Science, 2023)
Carrying out zakat is an obligation for all Muslims, which can provide material and spiritual prosperity for poor people. This research uses a qualitative descriptive method with data sources from poor families receiving ZIS assistance and data from BAZNAS Sidoarjo. Data collection methods include participant observation, semi-structured interviews, and documentation. The analysis was carried out by observing all BAZNAS Sidoarjo activities in distributing ZIS funds for education and analyzing interviews and related documentation. The research results show that the model for distributing zakat, infaq and alms funds by BAZNAS Sidoarjo includes school funding assistance, school equipment and school arrears, and has had a positive impact on the welfare of aid recipients. It appears that the ZIS distribution carried out by BAZNAS Sidoarjo in the education sector has been optimal, to help strengthen education.